Mechanically recovered poultry meat (MRPM) in chicken nuggets with antimicrobials - Dimailig, Leslie L.
ABSTRACT The development of chicken nuggets using mechanically recovered poultry meat (MRPM) had three major phases. Phase One dealt with the determination of an acceptable formulation for chicken nuggets. Two test formulations, with the necessary changes as indicated by the Focus Group Discussion (FGD), were produced then evaluated using paired difference test. No significant difference was found between the two samples, therefore the more economical formulation was chosen. Phase Two was on the determination of the optimum level of antimicrobial for incorporation in the chicken nuggets. Four test formulations were produced, one without antimicrobial (Formulation 859)and the other three (Formulations 628, 976 and 489) contained different proportions of antimicrobials. The efficiency of the antimicrobials was assessed using microbiological tests and sensory evaluations. Microbiological tests include total plate count (TPC), detection of coliform, Salmonella and Staphylococcus aureus. Both sensory and microbial analyses were performed twice, specifically one day and one week after production. Formulation 976 was found to be the most acceptable formulation. Phase Three was the evaluation of the physico-chemical properties of Formulation 976 of the chicken nuggets. The methods used were: Vacuum Oven Method for moisture determination; Soxhlet Method for determination of crude fat content; Kjeldahl Method for protein content; Weende Method for determination of crude fiber; Combustion Method for determination of ash; and Clegg Anthrone Method for determination of total available carbohydrates (TAC). Results showed that the raw chicken nuggets using MRPM contained 107.84% (db) moisture, 25.03% (db) crude fat, 45.67% (db) crude protein, 0.70% (db)crude fiber and 32.32% (db) TAC. The cooked chicken nuggets contained 80.85% (db) moisture, 24.07% (db) crude fat, 39.57% (db) crude protein, 0.39% (db) crude fiber, 4.88% (db) ash and 31.09% (db) TAC.